Membrane Formation by Dry-Cast Process: Model Validation Through Morphological Studies - Alsoy Altınkaya, Sacide; Yenal, Hacer; Alsoy Altınkaya, Sacide; Özbaş, Bülent (Elsevier Ltd., 2005)
Asymmetric membranes were prepared by dry-cast phase inversion technique from a cellulose acetate, acetone, water solution in order to assess the validity of the mathematical model recently developed by us. Based on the model predictions, general structural characteristics of the membranes were determined by plotting the composition paths on the ternary phase diagram and polymer concentration profile at the first moment of precipitation. Composition paths on the ternary phase diagram enable the assessment of whether a phase separation occurs and allow prediction of inception time and duration of the phase separation. The polymer distribution at the moment of precipitation provides a rough thickness of the high polymer concentration region near the interface and a pore distribution of the sublayer structure. The effects of polymer/nonsolvent ratio in the casting solution, the initial film thickness, evaporation temperature, relative humidity and velocity of air were investigated. Model predictions were compared with the morphological analysis conducted using scanning electron microscopy. Results show that diffusion formulation plays an important role in capturing the accurate structure of the membrane from the model predictions.
Keywords: Asymmetric membrane; Cellulose acetate; Dry-cast process; Morphological studies; Phase diagram